Can anyone ans this Q.?
Attachments:
![](https://hi-static.z-dn.net/files/d50/0495ba88f60ff0da2c363a4083601eb0.jpg)
Answers
Answered by
30
Step-by-step explanation:
Yes I can
sin theta + sin²theta = 1 (1)
sin theta = 1 - sin²theta
sin theta = cos²theta (2)
Cos²theta + cos⁴theta = sin theta + (cos²theta)²
= sin theta + (sin theta)² (from (2))
= sin theta + sin²theta
= 1 (from (1))
Answered by
9
Answer:
sin x + sin²x = 1
sin x = 1-sin² x
Also sin x = cos² x
cos²x + cos⁴x
= cos²x(1+cos²x)
= (1-sin²x)(1+1-sin²x)
= sin x(1+sin x)
= sin x + sin²x (this is given)
= 1
Note - I have used x in place of theta if you want you can write theta wherever x is used.
I hope you understand it.
Similar questions